INFLUENCE OF EUROPEAN MIGRATION (GERMAN, ITALIAN, AND AZORIAN) ON AGRICULTURAL PRACTICES AND RURAL CULTURE IN SANTA CATARINA: CULTURAL CONTINUITY, COMMUNITY ORGANIZATION, AND RURAL TRANSFORMATIONS - Machado dos Santos, Adelcio; Sprandel da Silva, Solange; Antonio Córdova Ransolin, Marco (Revista Gênero e Interdisciplinaridade, 2026)
This article examines the influence of European migrations (German, Italian, and Azorean) on agricultural practices and rural culture in Santa Catarina, considering agriculture not only as a productive activity but as a cultural expression. Based on a qualitative bibliographic review, the study investigates how these groups contributed to shaping specific territorialities, transmitting intergenerational agricultural knowledge, and structuring sociability through family organization, religiosity, and communal labor. Findings indicate that each migratory flow played a distinct role: Azoreans established subsistence systems and coastal religious traditions; Germans introduced productive rationalization, cooperativism, and disciplined land use; Italians strengthened family-based property structures, viticulture, and artisanal food production. These influences do not operate in isolation; instead, they generate ongoing processes of cultural hybridization in which traditions are reinterpreted amid contemporary transformations such as agricultural modernization, heritage tourism, and cultural patrimonialization. The study concludes that rural culture in Santa Catarina results from dynamic cultural syntheses that combine tradition and innovation, forming an intangible heritage in constant reconstruction. This research contributes to broader discussions on ethnicity, memory, and rural development in Brazil.